Servant Leadership in Islamic Education: An Integration of Knowledge Approach to Prophetic Leadership - Rinto Muhammadsyah Azhar (Nadwa: Jurnal Pendidikan Islam, 2026)
Contemporary Islamic educational institutions increasingly rely on Western-derived leadership theories that, while practically useful, remain epistemologically and theologically misaligned with the formative purposes of Islamic education. This article addresses this gap by developing an Islamic servant leadership framework grounded in Qur'anic exegesis and the Prophetic Sunnah within the Integration of Knowledge (IoK) methodology. Methodologically, the study employs IoK's double movement, interpreting Qur'anic principles in relation to contemporary educational leadership while rereading leadership challenges through those principles, with purposive ta'wīl serving as its primary hermeneutical approach. The analysis identifies four foundational concepts of Islamic servant leadership: servanthood ('ubūdiyyah) as the primary motivation for leadership, leadership as a divine trust (amānah), compassionate leadership (raḥmah) as the prophetic mode of relational engagement, and the serene soul (nafs muṭma'innah) as the indicator of successful servant leadership. These concepts are subsequently applied to three domains of educational leadership: ethical decision-making, authority and delegation, and strategic consultation (shūrā) alongside trust in God (tawakkul). The article argues that an IoK-grounded framework offers a theologically coherent and practically applicable alternative that addresses key conceptual limitations of secular servant leadership theory while strengthening leadership practice in Islamic educational institutions.